Thrombotic and Bleeding Complications Associated with Chemotherapy - McMahon, Brandon J.; Kwaan, Hau C. (Seminars in Thrombosis and Hemostasis, 2012)
It is well recognized that cancer patients have an increased risk of thrombosis and bleeding. Contributory factors to thrombotic complications include prothrombotic risks carried by many chemotherapeutic agents, type of cancer, stage of cancer, age, and comorbidities. Surgical procedures and the presence of an indwelling vascular device, often used as a mode of delivery for chemotherapy, further increase the risk. Correlative studies have demonstrated upregulation of coagulation in response to chemotherapeutics, and clinical studies have shown that various cancer treatments are independent risk factors for thrombotic complications. It has also been shown that patients who develop thrombosis during treatment have a worse overall prognosis. Mechanisms for chemotherapy and cancer-associated thrombosis are not well understood. Better insight into the mechanism for thrombosis may help better identify those cancer patients at highest risk, who may then benefit from up-front anticoagulant prophylaxis.
Keywords: adverse drug reactions; bleeding; cancer; chemotherapy; thrombosis